The Relationship between Maternal Nutritional Status and the Incidence of Stunting in Toddlers: Hubungan Status Gizi Ibu dengan Kejadian Stunting Balita - Maula, Liya Ni'matul; Yunita, Astri (Napande: Jurnal Bidan, 2023)
Background: Stunting is stunted growth and a nutritional problem. If there is a stunting problem, the community should receive quality education, provide a balanced nutritional intake, and improve the health status of children. Objective: to determine the relationship between nutritional status and the incidence of stunting among toddlers in Tulungrejo Pare Kediri. Method: The design of this research is analytical research using the Case Control Retrospective approach. The sampling technique was determined randomly. The sample used was a sample group of 55 cases and a control group of 55 toddlers who used a questionnaire measuring instrument. Results: The proportion of stunted (short) toddlers was 37.8% and very short (28.9%) occurred more frequently in mothers with poor nutritional status than in mothers with good nutritional status. The results of the chi-square analysis showed that p = 0.004 < 0.05, so Ho was rejected. Conclusion: There is a relationship between maternal nutritional status and the incidence of stunting under five, so mothers and the community should pay attention to the nutritional status of the mother before planning a pregnancy, paying attention to the mother's age and birth spacing so as not to give birth to babies with LBW or low birth length which can trigger stunting.